Essays on Planning and Economic Development - Center of Research on Underdeveloped Economies (Poland : Polish Scientific Publishers, 1965)
This book deals with planning and economic development. Its a compilation of essays, highlighting economic growth.
occ 15/01/2019
Loans
Keywords: Economic Planning; Economic Development